Blockholders And Debtholders Pressure On Earnings Management In Indonesia - Rustam Hanafi; Abdul Rohman; Dwi Ratmono (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study investigates the effect of blockholders and debtholders pressure on earnings management behavior. Both have potential conflicts of interest. Blockholders want dividends, and debtholders want payments and interest on their receivables. This study uses multiple linear regression to analyze 1,665 firm-year observations from the Indonesia Stock Exchange for the period 2013-2019. We find that blockholders have a significant positive effect on earnings management, indicating that blockholders tend to encourage management to manipulate earnings so that the company's performance looks good and the right to dividends will be better. Otherwise, debtholders have a significant negative effect on earnings management. It indicates that debtholders do not want earnings manipulation because, through debt covenants, they are safe with certainty in paying debts and interest. Meanwhile, for blockholders, debt covenants are a pressure because they have limited dividend payments. This study has complemented the previous perspective, where conflicts occur between blockholders and management, blockholders and minorities. This study shows that conflicts occur between blockholders and debtholders.